Impactos da pandemia de COVID-19: uma pesquisa-cuidado com mulheres mães trabalhadoras - Amador, Tatiana Doval (2025)
Although many studies consider the COVID-19 pandemic to be the greatest health crisis of modern times, revealing a wide range of serious social, political and economic problems and questioning ways of living, the protection of life and the persistence of social asymmetries, it is still necessary to discuss ways to address inequalities and gender-based violations experienced by working mothers in this context. This study addresses the lived experiences, knowledge, subjectivation processes and cultural dimensions, as well as the broader historical and political dimensions that permeate the trajectories of working mothers, with the aim of understanding the impacts of the COVID-19 pandemic on their lives and the coping, resistance and survival strategies they developed in this scenario. Based on intersectional black feminist perspectives, the study, which adopts an exploratory and qualitative methodological approach, employed interventional narrative research, involving the participation of working mothers from a poor peripheral community in the city of Santana de Parnaíba, in the state of São Paulo, Brazil. The data were produced using multiple strategies, namely: 1. procedures for identifying participant profiles and collecting data through an electronic form, individual interviews, occupational therapy groups and a subsequent data analysis; 2. care strategies with the research team, including the selection and monitoring of research assistants, in addition to their training and guidance throughout the process; and 3. narrative and creative production through field diaries, innovatice care practices, and the development of artistic creations. The results were organized into four thematic axes: 1. gender inequality at work during the COVID-19 pandemic; 2. motherhood and the burden of love in women's daily lives; 3. violence experienced and faced by women; 4. reinvention of daily life during the COVID-19 pandemic. In addition to enabling a critical analysis of these issues, the research process provided a space for care, allowing women to engage in new experiences and invent new forms of care in their lives, countering the structural violence they have been experiencing. This research contributed to the strengthening of Occupational Therapy as a political and social practice, promoting a new awareness based on respect, equity, dialogue, friendship and recognition of the rights and diversity of bodies and ways of living.